If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + -1(6b + 12) = -9b + 13 Reorder the terms: -3b + -1(12 + 6b) = -9b + 13 -3b + (12 * -1 + 6b * -1) = -9b + 13 -3b + (-12 + -6b) = -9b + 13 Reorder the terms: -12 + -3b + -6b = -9b + 13 Combine like terms: -3b + -6b = -9b -12 + -9b = -9b + 13 Reorder the terms: -12 + -9b = 13 + -9b Add '9b' to each side of the equation. -12 + -9b + 9b = 13 + -9b + 9b Combine like terms: -9b + 9b = 0 -12 + 0 = 13 + -9b + 9b -12 = 13 + -9b + 9b Combine like terms: -9b + 9b = 0 -12 = 13 + 0 -12 = 13 Solving -12 = 13 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -40=9g-4 | | 4x+3(x-5)=4(2x+3) | | 3x+3+x-7=180 | | .5x-7=x-5 | | 4n+8=13 | | 3.5d+8.75=5+4.25d | | -12=2x+6 | | 6h-4=32 | | 5c+8-4d-2-c= | | -3(x+1)+5=2(x-6) | | 2.5d+9.25=1+3.25d | | 8x+1=x+8 | | -16+x=-3x+8 | | 2(4x-1)-5=x-7 | | y-3=2x+2 | | 5+5x=23 | | 5+5+x=23 | | h+14.6=-14.6 | | 4q-q+3q-2q= | | s-5.9=19.2 | | 3(2x+5)=14x+7 | | 6.5=-3+j | | 5(x+1)=6x-11 | | 6a-8=7+a | | -3(2-x)=-15 | | F(x)=x^4-8x^3+18x^2+6 | | 3x-7x+5=3-5x | | 18x-28=x+380 | | 6+0.1x=0.15x+18 | | 10x+24=64 | | x+34+x+34=6x-28 | | 8(2x+1/4)=5(3-4x) |